جماليات الحيّز في الخطاب السردي الجزائري المعاصر رواية همس الرّماديّ )لمحمد مفلاح( أنموذجا مقاربة واصفة - سي أحمد عبد القادر (My University, 2018)
The novelist (Mohamed Meflah) is one of the contemporary Algerian writers who took the narrative writing that shows us an important aspect of the history of Algeria as well as the tragic reality experienced by Algeria during the liberation revolution in line with the various social, political and cultural developments that the country has known since independence until today, with a vision that carries many profound indications and artistic and aesthetic values, using space in his artwork in the manner of symbols and signals, which requires a narrative scientific study to explore its beauty through the different relationships that connect with other elements that make up an innovative novelist work - time, personality, language, event - as it is a central element as they interact within events and characters move and change over time, which makes it aesthetic on the literary text, through a literary language characterized by different levels.